Routledge handbook of Chinese architecture
1 online resource (xxv, 751 pages)
Keywords: "This handbook, representing the collaboration of 41 scholars, provides a multi-faceted exploration of roughly 6,000 years of Chinese architecture, from ancient times to the present. Thanks to its broad spectrum approach this volume formulates a thematic framework for investigating Chinese architecture, integrating previously fragmented topics and combining the scholarship of all major periods of Chinese history. By organising its approach into five parts this handbook: - Traces the practices and traditions of ancient China from imperial authority to folk culture. - Unveils a rich picture of early modern and republican China, revealing that modernization was already beginning to emerge. - Describes the social, intellectual, ideological, and formal enterprises of socialist architecture. - Frames a window on a complex and changing contemporary China by focusing on autonomy, state practices, and geopolitics of design, ultimately identifying its still evolving position on the world stage. - Examines the existing cultural and political theories to highlight potential avenues for future transformations in Chinese architecture which also retain Chinese identity. Providing a pioneering combination of ancient and modern Chinese architecture into one coherent study. This book is a must-read for scholars, students, and educators of Chinese Architecture, Architectural History and Theory and the Architecture of Asia"--